Copper 64–labeled daratumumab as a PET/CT imaging tracer for multiple myeloma - Caserta, Enrico; Chea, Junie; Minnix, Megan; Poku, Erasmus K.; Viola, Domenico; Vonderfecht, Steven; Yazaki, Paul; Crow, Desiree; Khalife, Jihane; Sanchez, James F.; Palmer, Joycelynne M.; Hui, Susanta; et al. (Blood, 2018)
As a growing number of patients with multiple myeloma (MM) respond to upfront therapies while eventually relapsing in a time frame that is often unpredictable, attention has increasingly focused on developing novel diagnostic criteria to also account for disease dissemination. Positron emission tomography/computed tomography (PET/CT) is often used as a noninvasive monitoring strategy to assess cancer cell dissemination, but because the uptake of the currently used radiotracer 18fluorodeoxyglucose (18F-FDG) is a function of the metabolic activity of both malignant and nonmalignant cells, the results frequently lack sufficient specificity. Radiolabeled antibodies targeting MM tissue may detect disease irrespective of cell metabolism. Hence, we conjugated the clinically significant CD38-directed human antibody daratumumab (Darzalex [Dara]) to the DOTA chelator and labeled it with the positron-emitting radionuclide copper 64 (64Cu; 64Cu-DOTA-Dara). Here, we show that 64Cu-DOTA-Dara can efficiently bind CD38 on the surface of MM cells and was mainly detected in the bones associated with tumor in a MM murine model. We also show that PET/CT based on 64Cu-DOTA-Dara displays a higher resolution and specificity to detect MM cell dissemination than does 18F-FDG PET/CT and was even more sensitive than were bioluminescence signals. We therefore have supporting evidence for using 64Cu-DOTA-Dara as a novel imaging agent for MM. •Daratumumab conjugated with 64Cu efficiently binds to CD38 on myeloma cells and was mainly detected in the bones of mice.•PET/CT based on 64Cu-radiolabeled daratumumab displays a higher resolution and specificity for detecting myeloma than does 18F-FDG PET/CT.